LOCAL APPROACH FOR EVALUATING HEAT TRANSFER OF PRISMATIC ELEMENTS ON A FLAT SURFACE - Suprun, T.T. (KU Publ., 2021)
Heat-exchange prismatic elements located on a flat surface are typical for many technical applications. The purpose of the work is to develop local approach for evaluating heat transfer of working surfaces based on local control of thermophysical parameters in characteristic zones of the working environment, using the methods of heat and mass analogy and hot-wire anemometry. The local approach allows more accurately diagnosing the types of flow in the boundary layer of a streamlined element and thereby, the temperature state of individual prismatic elements and the entire arrangement as a whole is determined more accurately. For calculating the local heat transfer of each face of the prism separately and the average surface heat transfer depending on the geometric and operating parameters equations of similarity are proposed.
Keywords: prismatic heat exchange surface; local thermophysical parameters